How we coach the hurdles - Hannan, S. (IFAC, 2012)
Powerpoint presentation of the author at the International Festival of Athletics Coaching in Glasgow, 2012 about training progression, performance progression, contact times, flight times, distance take-off to hurdle in hurdle running.